Sosialisasi Green Computing kepada Masyarakat sebagai Strategi Mengurangi Limbah Elektronik demi Sungai yang Lebih Bersih - Dedek Juliani Ritonga; Ermaliza; Siti Dian; Supiyandi (Raskha Media Group, 2025)
Electronic waste (e-waste) poses a serious threat to environmental sustainability, particularly to river ecosystems that serve as vital water sources and centers for community activities. However, public awareness regarding the dangers of e-waste and its proper management remains low, specifically in the Pantai Walikota area, Medan Tuntungan. This community service activity aims to socialize the principles of green computing to the local community as a strategic effort to reduce e-waste and maintain river cleanliness. The activity was conducted using a participatory education method, which included interactive lectures, discussions, and the distribution of educational brochures and posters to 10 residents living along the riverbank. The effectiveness of the program was measured through observation and direct feedback. The results showed a significant increase in public understanding; initially, only 25% of participants were familiar with green computing concepts. Post-socialization, 75% of participants gained new knowledge regarding e-waste hazards, and the majority expressed a willingness to adopt wiser device management practices. This study concludes that direct, contextual socialization in riverside areas is an effective strategy for fostering environmental responsibility and contributing to cleaner river ecosystems.